Training and written culture: the books of the land surveyor Francisco Falcón (1764) - García Cuadrado, Amparo (Historia y Memoria de la Educación, 2020)
This article approaches the study of the private library of the Murcian land surveyor Francisco Falcón de los Reyes, from the first half of the eighteenth century, which constitutes a clear example of the relationship between education and written culture. From the data extracted from a postmortem inventory and the subsequent appraisal and partition of goods among the heirs, we carried out a quantitative and qualitative analysis of said library. First, the text provides a biographical profile of this geometer, a descendant of slaves (new Christians), and describes the formative precariousness of these professionals in their time. The quantitative analysis of the bibliographic collection and its comparison with other private collections from similar socioeconomic fields indicate the importance of this particular collection. The qualitative study of authors and titles shows, on one hand, the high degree of mathematical training of the subject, who is shown to be a recipient of the fundamentally Valencian pre-illustrated reformist scientific mainstream, and, on the other hand, the purpose with which those books were incorporated into the funds of the collection. Together with the library, which we could call professional, due to its scientific nature, the inventoried religious matter in the form of printed documents makes up another interesting part of the collection, one of a catechetical nature in its various formative levels